Approximation of continuous functions defined on the real axis by generalized Zygmund operators - Ostrovskaya О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish estimates for upper bounds of deviations of generalized Zygmund operators on the classes of continuous (ψ, β)-differentiable functions defined on the real axis.